An Economic Study of Low Lying Inland Fish Farming in Selected Areas of Kishoreganj District (Progressive Agriculture, 2013)
The study was designed to examine the low lying inland fish farming practices of Karimganj upazila under Kishoreganj districts. Field level data were collected through direct interview using semi-structured questionnaire. Eighty sample farmers were selected purposively from the study areas. Six types of farming practices were identified in the study area among which only two types were prominent i.e., pond fish farming and Beel fish farming. Tabular, statistical and mathematical analyses were done to achieve the major objectives. The benefit cost ratio in Beel fish farming was 2.86 and in case of pond fish farming it was 1.95. Multiple regression model was used to explain the variation of gross return of pond and Beel fish farming and it was found that coefficients of human labour, feed, cowdung and manure had significant impact on gross return, whereas coefficients of feed, harvesting and making sanctuary had significant impact on gross return of Beel fish farming. Resource use efficiency was calculated by the ratio of marginal value product and marginal factor cost. Finally, the study identified some important problems of low lying inland fish farming and suggested probable solutions relating to the problems.DOI: http://dx.doi.org/10.3329/pa.v23i1-2.16619Progress. Agric. 23(1 & 2): 81 90, 2012